Tough Boris - Fox, Mem 1946-; Brown, Kathryn 1955- (Harcourt Brace, 1994)
Although he is a very tough pirate, Boris von der Borch cries when his parrot dies
Keywords: Trauer; Papageien; Seeräuber; Pirates / Juvenile fiction; Parrots / Juvenile fiction; Pirates / Fiction; Parrots; Pirates; JUVENILE FICTION / Action & Adventure / Pirates; JUVENILE FICTION / Animals / Pets; JUVENILE FICTION / Boys & Men; JUVENILE FICTION / Social Themes; JUVENILE FICTION / Special Needs; Fiction; Juvenile works; Easy books; Juvenile literature; Bilderbuch